Investigation of the Thin‐Film Phase Diagram of the Cr–Ni–Re System by High‐Throughput Experimentation. Issue 5 (27th December 2013) - Janghorban, Amin; Pfetzing‐Micklich, Janine; Frenzel, Jan; Ludwig, Alfred; Zschech, Ehrenfried
Abstract The Cr–Ni–Re system was investigated over the whole composition range using combinatorial fabrication methods combined with high‐throughput characterization techniques in order to establish its thin film phase diagram. After annealing at 940 and 1100 °C, the phase equilibrium was reached in the Ni‐rich part of the ternary in agreement with the published bulk phase diagram. Annealing the materials library at 940 °C is not sufficient to achieve the equilibrium state in the Re‐rich part of the system, however by annealing the materials library at 1100 °C the formation of expected phases (three solid‐solutions and a topologically close packed compound) could be observed. As a result of this study, a thin film phase diagram of the complete Cr–Ni–Re at 1100 °C was established, which is well comparable to the bulk phase diagram. This shows that the combinatorial thin film phase diagram approach is feasible and especially promising for materials systems with expensive and/or high melting point constituents.